Research on the use and problems of digital video camera from the perspective of schools primary teacher of Granada province - Pablo José García Sempere (Universidad de Granada, 2012)
The adoption of ICT in society and specifically in schools is changing the relationships and traditional means of teaching. These new situations require teachers to assume new roles and responsibilities, thereby creating new demands for training. The teaching body concurs that "teachers require both and initial and ongoing training in the use of digital video cameras and video editing." This article presents the main results of research that focused on the applications of digital video camera for teachers of primary education schools in the province of Granada, Spain.